Neonatal cephalic pustulosis. - Kansal, N.K. (European Journal of Pediatric Dermatology, 2015)
A 20-day-old newborn was first observed due to the presence of erythematous, papular and pustular lesions of the face: the identification of a "spaghetti and meatballs" finding on fresh mycological examination of the pus led to diagnose neonatal cephalic pustulosis. According to some Authors the latter is a disease in its own right, while others classify this disorder as neonatal acne.